Kinerja Pegawai Kelurahan dalam Pelayanan Administrasi Kependudukan di Kelurahan Lidah Wetan Kecamatan Lakarsantri Surabaya - Rahmadani, Salsabila Riska (VISA: Journal of Vision and Ideas, 2026)
Population administration services are a form of public service that directly addresses the fundamental needs of citizens, making their quality highly dependent on the performance of government officials at the village level. This study aims to analyze the performance of employees at Lidah Wetan Sub-District, Lakarsantri District, Surabaya, in providing population administration services, as well as to identify the supporting and inhibiting factors affecting their performance. This research employs a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving the village head, administrative staff, and community members as service users. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings indicate that the performance of village employees in delivering population administration services is generally adequate, particularly in terms of productivity and service quality. However, challenges remain in the aspects of responsiveness and responsibility, mainly due to limited human resources, high service demand, and the need for adaptation to digital-based service systems. Supporting factors include employee motivation, leadership support, and adequate facilities, while inhibiting factors consist of limited staff numbers, insufficient technological competence, and high public expectations regarding service speed. This study is expected to serve as an evaluative reference for village governments in improving employee performance and enhancing the quality of population administration services in a sustainable manner.